Novel timed and self-resistive heating shape memory polymer hybrid for large area and energy efficient application - Loeblein, Manuela (2020)
Shape memory polymers (SMPs) are a polymeric smart material that can register two or more temporary shapes and transform to one another through an external stimulus. Despite their compactness and customizability, SMPs haven't been able to be adopted for mainstream applications. Since the majority of SMPs are triggered by heat, and SMPs have a very poor thermal conductivity, large thermal gradients within the polymer appear which cause slow response, inhomogeneous heat distribution and thus non-uniform transformation of shapes and cracks. Many have attempted to improve their thermal performance through the incorporation of filler-based nanomaterials. However, the outcome is ineffective as the spatial dispersion of fillers within the SMP is inhomogeneous and leads to performance loss. Contrastingly, the herein presented new class of nanocomposite-SMP, composed by 3D-foam fillers, showcase a much more efficient SMP adaptable to larger area with faster transformation speed and without any performance loss. Furthermore, the improved thermal properties lead to a decrease in required input energy, as well as render the SMP a self-heating capability which can be further designed into timed multi-step SMP behavior.